Functional constipation in children – evaluation and management - Gibas-Dorna, Magdalena; Piątek, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Almost 1/3 of gastrointestinal consultations are related to constipation, and over 90% of them are of functional origin. Proper diagnosis and adequate treatment (both nonpharmacological and pharmacological) may limit the number of specialist visits and can be beneficial for therapeutic effects. The treatment is long lasting and requires unique discipline of parents/guardians and coordination supervised by the referring doctor. This paper presents the most important aspects of diagnostic and therapeutic processes regarding functional constipation in neonates and toddlers.